The Influence of Individual Characteristics, Distance, Cost, and Tangibles on Decisions to Choose a Place of Birth - Bantoyot, Feby; Syaodih, Erliany; Handayani, Nining (ProBisnis : Jurnal Manajemen, 2025)
Quality and affordable delivery services are key to reducing maternal and infant mortality rates. This study aims to analyze the influence of individual characteristics, distance, cost, and tangible quality on mothers' decisions regarding the choice of delivery location at the Bonebakal Health Center in Central Sulawesi. The study employed a quantitative approach with a cross-sectional design, involving 35 pregnant women as respondents who were selected purposively. Data analysis was carried out using the chi-square test and multiple logistic regression. The results showed that age, education, distance, and tangible quality had a significant influence on the decision to choose a place of delivery (p <0.05). Tangible was the most dominant factor with an OR value of 5.783. In contrast, occupation, income, and cost did not have a significant effect in the final model. The regression model was proven valid and explained 74.5% of the variation in decisions (Nagelkerke R² = 0.745). These results highlight the importance of enhancing the physical quality of delivery facilities and education tailored to maternal characteristics, in order to support the selection of a safe and standardized place of delivery.